Implications for European physical education teacher education during the COVID-19 pandemic: a cross-institutional SWOT analysis - O`Brien, W.; Adamakis, M.; O` Brien, N.; Onofre, M.; Martins, J.; Dania, A.; Makopoulou, K.; Herold, F.; Ng, K.; Costa, J. (European Journal of Teacher Education, 2020)
The present study, using a sample of Physical Education Teacher Education (PETE) representatives from five Higher Education European institutions (England, Finland, Greece, Ireland, and Portugal) sought to investigate the proposed measures of change required for programme delivery during the academic year of 2020-21. Each team completed a SWOT (strengths, weaknesses, opportunities and threats) examination through inductive cross-analysis, using a deductive structure, following the dimensions of: PETE Programme; PETE Staff; PETE Students. The findings presented at a case level show how each PETE programme is seeking to manage an important tension between the experiential nature of Physical Education (PE) as a subject, in light of the institutional and external constraints towards online and blended approaches. Having identified the thematic variables for PETE at an overall programme, staff and student level, the SWOT analysis heightened PETE pedagogue understanding of the subject beyond `physical` contact spaces, for meaningful third-level teacher education delivery.